Peran Influencer Melalui Fitur Tiktok Shop dalam Meningkatkan Keuntungan Brand Make Up - Jesika, Maria; Eni, Rahel; Wayangkau, Yokbeth (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
In the ever-evolving digital era, social media platforms have become an important part of brands’ marketing strategies to reach a wider audience. The leading platform today is TikTok which has attracted the attention of many brands and consumers around the world. TikTok is not only a platform for entertainment and creativity, but also the main stage for influencers who have a big influence on consumer behavior and preferences. In this context, the TikTokShop feature emerged as an innovation that allows brands to sell products directly to TikTok users through videos created by influencers. Collaboration between influencers and brands through TikTokShop provides new opportunities for brands to expand reach, increase consumer awareness, and ultimately increase sales. This research discusses the role of influencers in increasing brand profits through the TikTokShop feature. The research was conducted by analyzing interactions between influencers and brands, as well as their impact on increasing product sales through TikTokShop.